Pengembangan Kapasitas Institusi Sekolah dalam Mendukung Program Makan Bergizi Gratis di SMP Negeri 7 Jember - Zainuri Zainuri; Isti Fadah; Fajar Wahyu Prianto; Dwi Perwitasari Wiryaningtyas; Mohamad Rifqi Fathoni (Jurnal Pelayanan Masyarakat, 2025)
The Free Nutritious Meal Program (MBG) is a national initiative to strengthen human resource quality, yet its success depends on schools’ capacity to plan, manage, and sustain implementation. This community engagement program aims to build the institutional capacity of SMP Negeri 7 Jember in planning and executing MBG, enhancing nutrition literacy among teachers, students, and parents, and fostering a sustainable collaboration model with relevant stakeholders. Using a Participatory Rural Appraisal (PRA) approach with a Plan–Act–Observe–Reflect cycle, the activities included baseline mapping of nutrition management, development of an action plan, training and mentoring for MBG SOP formulation, implementation of healthy eating practices, and reflective sessions for sustainability planning. The program resulted in improved managerial capacity, as evidenced by the development and initial application of MBG SOPs, stronger internal coordination, and increased nutrition knowledge, based on pre- and post–training scores. Parental involvement strengthened alignment between school and home practices, supporting the emergence of a healthy nutrition culture.